1993
DOI: 10.1021/ja00055a073
|View full text |Cite
|
Sign up to set email alerts
|

The chemical nature of amavadin

Abstract: 807leaves little doubt that the acylated phenylisoserine side chain of these taxoids is synthesized via path a of Scheme I. Unexpectedly, in both experiments 1, but not 2, also showed a pronounced M + 10 peak, as well as a P + 10 satellite for the m / z 286 fragment representing the side chain. Hence, the aromatic ring of 4a and Sa must have also becn incorporated into the benzoyl group of the 1 side chain. Together with the non-incorporation of 7a this suggests the operation of a new pathway, other than the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 2 publications
0
78
0
1
Order By: Relevance
“…This assignment is corroborated by the observation of 51 V high frequency shifts of the signals for the dimer with respect to those of the monomer in other systems, such as the oxovanadium alkoxides VO(OR) 3 or vanadate complexes of hydroxy acids such as glycerate or lactate. [30] In a highly concentrated methanol solution, this compound precipitates as red crystals, which were analysed by X-ray crystallography.…”
Section: Nmr Spectroscopic Studiesmentioning
confidence: 69%
See 1 more Smart Citation
“…This assignment is corroborated by the observation of 51 V high frequency shifts of the signals for the dimer with respect to those of the monomer in other systems, such as the oxovanadium alkoxides VO(OR) 3 or vanadate complexes of hydroxy acids such as glycerate or lactate. [30] In a highly concentrated methanol solution, this compound precipitates as red crystals, which were analysed by X-ray crystallography.…”
Section: Nmr Spectroscopic Studiesmentioning
confidence: 69%
“…[1,2] It is present in some biological systems in high concentrations, where it seems to have a relevant role, such as in the Amanita muscaria mushroom as the amavadin complex [3] and in some ascideas in the form of tunichromes. [4] Vanadium is the cofactor of some enzymes, like the vanadium-dependent haloperoxidases in al-3586 of the V 2 Y 2 L 2 and V 1 Y signals decrease sharply, and a broad signal at -488 ppm appears, corresponding to the original V V trimer complex, which is the only species present in 94 % water.…”
Section: Introductionmentioning
confidence: 99%
“…The tridentate ONS ligand forms one six membered and one five membered chelate ring at the vanadium(V) acceptor center, the corresponding bite angles being 82.31°(9) and 80.58° (11), respectively the two axial positions are occupied by the oxido oxygen atom O35 and nitrogen atom N23 of the secondary ligand bipyridine. The short V1-O35 distance of 1.595(3) Å indicate the presence of vanadium oxygen double bond commonly found in five and six coordinated complexes of V(IV) and V(V).…”
Section: Description Of Crystal Structure [Vo(22 0 -Bipy)l] (5)mentioning
confidence: 99%
“…3 Furthermore, the vanadium atom is configurationally labile in solution and the complex is prone to epimerization [18,23,24]. The interconversion between D and K diastereomers occurs via a flip of one of the N-O moieties (Fig.…”
Section: Proposed Model To Account For the Isomerism And Symmetry In mentioning
confidence: 99%
“…5a) [18,23]. It has previously been shown that only minimal structural changes take place upon the one-electron oxidation to vanadium(V) when the amavadin ligand 1 [7,24] In 'meso-amavadin' the situation appeared to be more complicated because the presence of (R) and (S) stereogenic centers in the ligands breaks the symmetry of the molecule. This results in eight different possibilities to arrange the two meso-ligands around the vanadium, instead of the two possibilities for the (S,S)-ligands.…”
Section: Proposed Model To Account For the Isomerism And Symmetry In mentioning
confidence: 99%